The economics of LBOs: evidence from the syndicated loan market - Pinto, João (2021)
This paper surveys extant literature on Leveraged Buy-Outs (LBOs). In addition to describing the economic motivation for the use of LBOs, this paper provides details on LBO characteristics and players, it presents the recent trends of the market, and provides statistics in relation to syndicated loans extended to LBOs worldwide in the 2000-2020 period. LBOs create economic value by reducing agency problems, improving operating performance, increasing interest tax shields, reducing transaction costs, and allowing for takeover defenses. However, LBOs also have drawbacks, namely: high complexity, off-balance sheet treatment, asymmetric information problems, expropriation of nonequity stakeholders, and increased financial distress. Statistical analysis shows that loan contractual characteristics differ significantly in the pre- versus the crisis period, and both loan spread and major pricing factors differ significantly for deals closed in the U.S. vis-à-vis Europe. In addition, loans to LBOs arranged for U.S. borrowers have higher spreads and upfront fees and have higher loan size to deal size ratios when compared with loans arranged for borrowers located in Europe. On the contrary, loans closed in the U.S. have a much shorter average maturity and are much less likely to be subject to currency risk and to be closed as term loans.